Prognostic role of selection criteria for liver transplantation in patients with hepatocellular carcinoma: a network meta-analysis - Lozanovski, Vladimir J.; Ramouz, Ali; Aminizadeh, Ehsan; Ali-Hasan-Al-Saegh, Sadeq; Khajeh, Elias; Probst, Heike; Picardi, Susanne; Rupp, Christian; Chang, De-Hua; Probst, Pascal; Mehrabi, Arianeb (BJS open, 2022)
Patients with hepatocellular carcinoma (HCC) are selected for transplantation if they have a low tumour burden and low risk of recurrence. The morphometric Milan criteria have been the cornerstone for patient selection, but dynamic morphological and biological tumour characteristics surfaced as an encouraging tool to refine the selection of patients with HCC and to support the expansion of the Milan criteria. The outcomes of the most prevalent models that select patients with HCC for liver transplantation were analysed in this study, which aimed to identify the selection model that offered the best recurrence-free and overall survival after transplantation.Studies that compared Milan, University of California San Francisco (UCSF), up-to-seven (UPTS), alpha-fetoprotein (AFP), and MetroTicket 2.0 (MT2) models were included. One-year, 3-year, and 5-year recurrence-free and overall survival rates of patients selected for transplantation using different models were analysed.A total of 60 850 adult patients with HCC selected for liver transplantation using Milan, UCSF, UPTS, AFP, or MT2 criteria were included. Patients selected for transplantation using the MT2 model had the highest 1-, 3-, and 5-year recurrence-free survival. In addition, patients selected for transplantation using MT2 criteria had the best 1- and 3-year overall survival, whereas patients selected for transplantation using the Milan criteria had the best 5-year overall survival rates.The MT2 model offered the best post-transplant outcomes in patients with HCC, highlighting the importance of considering tumour morphology and biology when selecting patients with HCC for liver transplantation.
Accepted: November 07, 2021
Gesehen am 21.03.2022